2011
DOI: 10.1093/aje/kwr095
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Socioeconomic Context and Cognitive Decline Among Older Mexican Americans: Results From the Sacramento Area Latino Study on Aging

Abstract: In 1 previous study, it was shown that neighborhood socioeconomic disadvantage is associated with cognitive decline among Latinos. No studies have explored whether and to what extent individual-level socioeconomic factors account for the relation between neighborhood disadvantage and cognitive decline. The purpose of the present study was to assess the influence of neighborhood socioeconomic position (SEP) on cognitive decline and examine how individual-level SEP factors (educational level, annual income, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
77
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 34 publications
11
77
1
2
Order By: Relevance
“…Accompanying this overall level difference, however, there were no significant differences in the rate of cognitive change over time (i.e., decline) for respondents who resided in neighborhoods with an older age structure. The lack of differences in cognitive trajectories by neighborhood age structure over time is consistent with other work examining socioeconomic context and cognition using longitudinal data (Al Hazzouri et al, 2011; Rosso et al, 2016) and could be for any of a number of reasons. One possibility could be that differential mortality would select a healthier sample over time, a pattern that has been shown, for example to produce cross-overs in health and mortality by race and socioeconomic status (Goldman, 1993; Palloni & Ewbank, 2004; Vaupel et al, 1979; Zajacova & Burgard, 2013).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Accompanying this overall level difference, however, there were no significant differences in the rate of cognitive change over time (i.e., decline) for respondents who resided in neighborhoods with an older age structure. The lack of differences in cognitive trajectories by neighborhood age structure over time is consistent with other work examining socioeconomic context and cognition using longitudinal data (Al Hazzouri et al, 2011; Rosso et al, 2016) and could be for any of a number of reasons. One possibility could be that differential mortality would select a healthier sample over time, a pattern that has been shown, for example to produce cross-overs in health and mortality by race and socioeconomic status (Goldman, 1993; Palloni & Ewbank, 2004; Vaupel et al, 1979; Zajacova & Burgard, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…Differences in the socioeconomic conditions in neighborhoods with more as compared to fewer older adults, for instance, could explain differences in neighborhood age structure and health, particularly if neighborhoods with a greater percentage of older adults are more advantaged. There is already a large body of work suggesting that neighborhood socioeconomic status (NSES) is linked to a variety of health outcomes, including cognition (Al Hazzouri et al, 2011; Basta et al, 2008; Clarke et al, 2012; Clarke et al, 2015; Shih et al, 2011; Wee et al, 2012; Wu et al, 2015). In addition, there is some evidence that older adults may live in areas with better NSES.…”
Section: Introductionmentioning
confidence: 99%
“…Higher NSEP scores indicated higher neighborhood socioeconomic status. Further details on the statistical methods resulting in NSEP have been published elsewhere (Zeki Al Hazzouri et al, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…Positive associations have been documented between late life cognition and various indicators of childhood SES, including county literacy rate (Wilson, Scherr, Hoganson, et al, 2005), urban versus rural upbringing (Zhang, Gu, & Hayward, 2008), parental education and occupation (Everson-Rose, Mendes de Leon, Bienias, Wilson, & Evans, 2003), and self-reported childhood SES and household size (Wilson, Scherr, Bienias, et al, 2005). There is substantial covariation between education and childhood SES (e.g., Everson-Rose, et al, 2003) but some studies have suggested they each make unique contributions to cross-sectional performance on measures of late life cognition (e.g., Zeki Al Hazzouri, Haan, Osypuk, Abdou, Hinton & Aiello, 2011). However, many of the same studies reported no influence of childhood SES on cognitive change (Everson-Rose, et al, 2003; Wilson, Scherr, Bienias, et al, 2005), particularly when taking into account other correlated variables (Zeki Al Hazzouri, Haan, Osypuk, Abdou, Hinton & Aiello, 2011).…”
mentioning
confidence: 99%
“…There is substantial covariation between education and childhood SES (e.g., Everson-Rose, et al, 2003) but some studies have suggested they each make unique contributions to cross-sectional performance on measures of late life cognition (e.g., Zeki Al Hazzouri, Haan, Osypuk, Abdou, Hinton & Aiello, 2011). However, many of the same studies reported no influence of childhood SES on cognitive change (Everson-Rose, et al, 2003; Wilson, Scherr, Bienias, et al, 2005), particularly when taking into account other correlated variables (Zeki Al Hazzouri, Haan, Osypuk, Abdou, Hinton & Aiello, 2011). …”
mentioning
confidence: 99%